The effectiveness of strength-based counseling on the tendency toward marital infidelity and self-compassion of conflicted couples - Movahedrad , Fatemeh; Sayed Alitabar , Sayed Hadi; Mohammadi , Alireza; Hosseinifard , Vida (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: It is natural for differences and conflicts to arise between husband and wife. Due to the nature of spouses’ activities, it sometimes happens that differences of opinion occur or needs are not met. As a result, spouses feel angry, disappointed, and unhappy towards each other. The current research aimed to determine the effectiveness of strength-based counseling on conflicted couples’ tendency toward marital infidelity and self-compassion. Methods and Materials: It was quasi-experimental with a pre-test and post-test design with an experimental group, a control group, and a three-month follow-up period. The statistical population of the research included all couples referring to a private counseling center in District 10 of Tehran. For sampling, 30 couples were selected and randomly assigned to two experimental groups (15 couples) and a control group (15 couples) using the available sampling method. This research used the strength-based counseling package compiled by Parsakia and Darbani (2022). Also, in order to collect data, Neff’s self-compassion scale (2003) and Bashirpour et al.’s marital infidelity questionnaire (2018) were used. Findings: The results of the data analysis showed that strength-based counseling significantly increased self-compassion scores (F = 13.08) and decreased the scores of the tendency toward marital infidelity of the experimental group (F = 9.52). Also, Bonferroni’s post hoc test results indicated good stability of these effects. Conclusion: Therefore, the strength-based approach can increase the self-compassion of conflicted couples and decrease their tendency toward committing marital infidelity. Conclusion: It can be concluded that parent-child interaction training was effective on behavioral problems and aggression of children with ADHD symptoms, and this effect was stable